Designing together: collaborative approaches to online integration training for immigrants - Hartikainen, Anita (fi=Turun yliopisto|en=University of Turku|, 2026)
This dissertation explores collaborative approaches to designing online integration training for immigrants, emphasising the significance of co-design in creating inclusive and effective learning environments. These environments aim to support immigrants in acquiring language and cultural skills as well as employability competencies. The research is situated in the Finnish context, where integration training plays a crucial role in fostering immigrants’ societal participation and employment opportunities. The research is grounded in a design science research approach, which involves the creation, evaluation, and iterative development of educational artefacts that integrate technology as part of the learning process. The theoretical framework combines the TPACK model (Technological Pedagogical Content Knowledge) with a socioconstructivist learning perspective, emphasizing the integration of technology, pedagogy, and content knowledge alongside collaborative knowledge building. Central to the study is the examination of teachers’ competencies as integration trainers and their role as part of an online community of practice for educational development. The central research question was: How to design fully online integration training based on the Finnish Act on the Integration of Immigrants? The findings highlight the importance of learning communities, comprising teachers, learners, and educational developers, in driving innovation and fostering inclusivity in integration training. These communities provide a foundation for user-centered and culturally sensitive learning solutions while emphasizing digital accessibility and collaborative design processes. This research demonstrates how such approaches enhance the inclusiveness and sustainability of learning environments. The research presents a model that was co-developed in an authentic setting and demonstrates how online integration training can be designed to support learners with diverse backgrounds and needs. The dissertation offers practical recommendations for educational developers, policymakers, and technology designers, emphasizing the importance of scalable and adaptable solutions for integration training in diverse learning contexts.

Yhdessä muotoillen: yhteistoiminnallisia lähestymistapoja kotoutumiskoulutuksen verkkototeutukseen Tässä väitöskirjassa tarkastellaan yhteistyöhön perustuvia lähestymistapoja maahanmuuttajien verkossa toteutettavan kotoutumiskoulutuksen suunnittelussa. Tutkimus painottaa yhteissuunnittelun merkitystä osallistavien ja tehokkaiden oppimisympäristöjen kehittämisessä, jotka tukevat maahanmuuttajien kieli- ja kulttuuriosaamista sekä työelämävalmiuksia. Tutkimus sijoittuu Suomen kontekstiin, jossa kotoutumiskoulutus on keskeinen osa maahanmuuttajien yhteiskunnallista osallistumista ja työllistymistä. Tutkimuksen lähtökohtana on design science research -lähestymistapa, jonka avulla luodaan, tutkitaan, arvioidaan ja kehitetään edelleen koulutusartefakteja, jotka hyödyntävät teknologiaa osana oppimista. Teoreettinen viitekehys perustuu TPACK-malliin (Technological Pedagogical Content Knowledge) ja sosiokonstruktivistiseen oppimiskäsitykseen. Tämä yhdistelmä korostaa teknologian, pedagogiikan ja sisällön integrointia sekä yhteisöllistä tiedonrakentelua. Keskeisessä roolissa ovat opettajien kompetenssit kotoutumiskouluttajina osana verkossa toimivaa koulutuksen kehittämisyhteisöä. Tutkimuksen keskeiseksi tutkimuskysymykseksi muodostui: Kuinka luoda täysin verkossa toteutettava kotoutumiskoulutus, joka tukee osallisuutta ja kotoutumista kotoutumislain ja opetussuunnitelman mukaisella tavalla? Tulokset tuovat esiin oppivien yhteisöjen merkityksen koulutuksen kehittämisessä ja osallisuuden vahvistamisessa. Oppivat yhteisöt, jotka koostuvat opettajista, oppijoista ja koulutuksen kehittäjistä, tarjoavat perustan käyttäjälähtöisille ja kulttuurienvälisesti sensitiivisille oppimisratkaisuille. Lisäksi tutkimus korostaa digitaalisen saavutettavuuden ja yhteisöllisen suunnittelun merkitystä, koska nämä edistävät oppimis-ympäristöjen osallistavuutta ja kestävyyttä. Tutkimus esittää yhteiskehittämällä autenttisessa ympäristössä toteutetun mallin, miten kotoutumiskoulutusta verkossa voidaan muotoilla kaikenlaisille oppijoille. Väitöskirja tarjoaa suosituksia koulutuksen kehittäjille, päätöksentekijöille ja teknologiakehittäjille, painottaen skaalautuvien ja joustavien ratkaisujen merkitystä kotoutumiskoulutuksen kehittämisessä monimuotoisissa oppimisympäristöissä.